UJI EFEKTIVITAS EKSTRAK ASETON DAUN KAYU MANIS (Cinnamomum burmanni Blume) TERHADAP JAMUR FUSARIUM SOLANI PENYEBAB PENYAKIT BUSUK BATANG PADA BUAH NAGA (HYLOCEREUS SP.) SECARA IN VITRO - Darmadi, Anak Agung Ketut; Ginantra, I Ketut; Joni, Martin (Metamorfosa: Journal of Biological Sciences, 2017)
This research heads for examining the effectiveness of acetone extract of cinnamon leaf  ( Cinnamomum burmanni Blume) to the growth of Fusarium soloni fungus. Cinnamon leaf which was used in this research grows in Bedugul village Tabanan regency Bali province. The extract effectiveness experiment of cinnamon leaf to the fungus experiment  was carried out by well difusion method in Biopesticide Laboratory of Agriculture Faculty Udayana University, by using the complete random plan consists of 6 treatments and 4 times refrains. The concentration treatment of acetone  extract of cinnamon leaf obviously (P<0.05) can impede the growth of colony, biomass and establishment of experiment fungus spore i.e. Fusarium soloni in accordance with in-vitro by PDA and PDB media. Extract minimum blocked energy of cinnamon leaf in experiment fungus i.e. 0,5%. The extract of cinnamon leaf obviously can impedethe growth of colony, spore establishment and biomass establishment of experiment fungus. In extract concentration treatment 0.5% obviously can impede the colony growth of experiment fungus, spore establishment and fungus biomass establishment i.e. each of them in amount of  17,3%, 41,45% and 7,94% if they are compared by the control. The higher extract concentration then the blocked energy is the bigger.
Keywords: cinnamon leaf extract, compound antifungal, Fusarium soloni fungus